Knowledge Mapping of the Links Between the Gut Microbiota and Heart Failure: A Scientometric Investigation (2006–2021) - Mu, Fei; Tang, Meng; Guan, Yue; Lin, Rui; Zhao, Meina; Zhao, Jiaxin; Huang, Shaojie; Zhang, Haiyue; Wang, Jingwen; Tang, Haifeng (Frontiers in Cardiovascular Medicine, 2022)
Background: Gut microbiota have important research value and broad application prospects in the heart failure field. This study provides information on the latest progress, evolutionary path, frontier research hotspots, and future research developmental trends in this field. Methods: Research datasets were acquired from the Web of Science Core Collection (WoSCC) from January 1, 2006 to December 31, 2021. Microsoft Excel and CiteSpace (5.6 R2) was used to perform collaboration network analysis, co-citation analysis, co-occurrence analysis, and citation burst detection. Results: A total of 873 publications in the WoSCC database met the requirement. The data indicated a steady growth and an exponential increase in publication numbers. Articles were the primary publication type with the United States as the leading country and the center of national collaboration. Cleveland Clinic and Nathalie M Delzenne provided the leading influence with publications, the cooperation between the institutes and authors were relatively weak. Moreover, gut microbiota, heart failure, risk factor, obesity and inflammation were some of the high frequency keywords in co-occurrence cluster analysis and co-cited reference cluster analysis. Burst detection analysis of top keywords showed that TMAO, bile acid, blood pressure, hypertension and fermentation were the new research foci on the association between gut microbiota and heart failure. Strategies to improve the intestinal microbiota are expected to be new approaches for the treatment of heart failure. Conclusions: This comprehensive bibliometric study indicates that the structured information may be helpful in understanding research trends in the link between gut microbiota and heart failure, and locating research hotspots and gaps in this domain, especially further advances in this field have a huge potential for yielding significant breakthroughs in the development of novel therapeutic tools for metabolic modulation of heart failure.